1995
DOI: 10.1016/s0892-1997(05)80232-2
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic concomitants of emotional expression in operatic singing: The case of lucia in Ardi gli incensi

Abstract: Sununary: Two excerpts from the cadenza in Ardi gli incensi from Donizetti's opera Lucia di Lammermoor were acoustically analyzed for five recorded versions of the cadenza by Toti dal Monte, Maria Callas, Renata Scotto, Joan Sutherland, and Edita Gruberova. These acoustic parameters of the singing voices were correlated with preference and emotional expression judgments, based on pairwise comparisons, made by a group of experienced listenerjudges. In addition to showing major differences in the voice quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…On the other hand, some vocal tract shapes are similar between speakers for some emotional states or modes of production, so that vocal tract resonances can participate, among other cues, in the perception, from the sound of the voice only, of smiling (Tartter, 1990), of different emotions (Siegwart andScherer, 1995, Burkhardt andSendlmeier, 2000) or of vocal effort (Liénard and Di Benedetto, 1999;Eriksson and Traunmuller, 2002).…”
Section: Consequences For Speech Phonemes and Voice Qualitymentioning
confidence: 99%
“…On the other hand, some vocal tract shapes are similar between speakers for some emotional states or modes of production, so that vocal tract resonances can participate, among other cues, in the perception, from the sound of the voice only, of smiling (Tartter, 1990), of different emotions (Siegwart andScherer, 1995, Burkhardt andSendlmeier, 2000) or of vocal effort (Liénard and Di Benedetto, 1999;Eriksson and Traunmuller, 2002).…”
Section: Consequences For Speech Phonemes and Voice Qualitymentioning
confidence: 99%
“…However, ways of getting closer to ecologically valid settings may be to analyze existing recordings of performances or to observe performers, from the preparation of a piece to the actual performance in a concert. Siegwart and Scherer (1995) studied emotional expression in opera singing by analyzing existing recordings by well-known artists. They found that (a) different interpretations elicited different listener ratings of emotional expressiveness, (b) voice samples differed substantially with respect to acoustic cues, and (c) listeners' judgments could be successfully predicted on the basis of the acoustic cues.…”
Section: Limitations Of the Findingsmentioning
confidence: 99%
“…Another method used to investigate how the emotional meaning is conveyed in singing voice has been to compare recordings of a same song performed by various singers and analyze listeners' judgments of emotions perceived for each particular performer. Siegwart and Scherer (1995) and Howes et al (2004) found that listeners' preferences and emotion judgments were indeed associated with specific acoustics characteristics. Correlations between different acoustic parameters and listeners' perception of emotions in singing voice (as well as in music in general) can also be studied by investigating the listeners' emotion judgments of sounds that had each of different parameters systematically and independently manipulated (Scherer and Oshinsky, 1977;Kotlyar and Morozov, 1976).…”
Section: Introductionmentioning
confidence: 96%